Torrfoder till katt : påverkan och konsekvenser - Blixt, Patrik (SLU/Dept. of Animal Environment and Health (until 231231), 2012)
The cat has evolutionary become an obligate carnivore. Today it is common to feed the cat a dry food. Studies have shown that the dry formula can have negative consequences for the cat. A literature study where conducted to investigate whether the cats origin makes it incapable to compensate for the changes a dry food entails. The impact and implications regarding water intake, energy intake and blood glucose concentration when feeding the cat dry food where examined. The results shows that when dry food is fed, urine volume decreases and the water intake for every gram food consumed is less compared to when food with higher water content is fed. This is linked with dry food increasing the risk for developing FLUTD, even though dry food is not the only factor in the development. The results show that it is not recommendable to feed dry food if the cat has been diagnosed with FLUTD. The energy density of dry food impacts the energy intake but not profoundly enough to be the only factor for the high prevalence of overweight cats. For the already overweight cat, dry food is not the best food formula to use. Both for weight loss and weight maintenance, food with less energy density is positive. Although the carbohydrate content of dry food doesn’t impact the concentration of glucose in the blood, it is not an advantage for the cat with diabetes mellitus to have high carbohydrate content in the food. Less carbohydrate, mimicking the content of the cat’s natural food, has shown to be more effective than a higher carbohydrate content in the treatment of diabetes mellitus.